Squamous Cell Carcinoma Developing from a Testicular Epidermal Cyst: A Case Report and Literature Review - Ryo Kasahara; Ryosuke Tajiri; Kota Kobayashi; Masahiro Yao; Kazuo Kitami (Case Reports in Urology)
A 50-year-old Japanese man with a two-year history of a painless right scrotal mass visited our hospital. Considering laboratory findings and computed tomography, the patient was diagnosed with an uncharacteristic testicular tumor. No metastases were present on radiographic study at the first visit. Emergent high radical orchiectomy was performed, and the tumor was identified as a squamous cell carcinoma (SCC) of a testicular epidermal cyst. He is alive without recurrence or metastasis six months after surgery. Testicular SCC is an extremely rare tumor. This is the third case of testicular SCC associated with an epidermal cyst in English literature.